A needle in a haystack: the new genus Bernadottea (Diptera: Cecidomyiidae, Winnertziinae) with four new species in the Old World - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2018)
A new genus of Winnertziini (Cecidomyiidae: Winnertziinae) named Bernadottea gen. nov. is introduced to absorb four new species from various different parts of the Old World: B. natalensis sp. nov. from South Africa, B. honshuensis sp. nov. from Japan, and B. pahangensis sp. nov. and B. selangorensis sp. nov. from Malaysia. Bernadottea are distinguished from previously known Winnertziini by the unusually complex genitalia of males, and from most members of this tribe by the absence of the fourth medial vein (M4). Another feature of Bernadottea is their rare occurrence in samples of Winnertziini taken by hand or by traps, a circumstance presumably expressing their scarcity in nature, at least at ground level. The new taxa are described based on the morphology of males, while females and larvae remain unknown.